2011
DOI: 10.1016/j.jcin.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Continued Benefit From Paclitaxel-Eluting Compared With Bare-Metal Stent Implantation in Saphenous Vein Graft Lesions During Long-Term Follow-Up of the SOS (Stenting of Saphenous Vein Grafts) Trial

Abstract: During long-term follow-up, use of PES was associated with significantly better clinical outcomes than BMS in SVG lesions. (Stenting of Saphenous Vein Grafts Trial [SOS]; NCT00247208).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 37 publications
1
60
1
2
Order By: Relevance
“…Specifically, rates of MACE at four years in the present study (46%) were similar to those reported among PES-treated patients in the randomised Stenting of Saphenous Vein Grafts (SOS) trial at 35 months of follow-up (54%) 14 . Similarly, in the Extended Duration of the Reduction of Restenosis In Saphenous vein grafts with Cypher stent (DELAYED RRISC) study 15 , rates of MACE amounted to 58% among SES-treated patients at a median follow-up of 32 months.…”
Section: Discussionsupporting
confidence: 85%
“…Specifically, rates of MACE at four years in the present study (46%) were similar to those reported among PES-treated patients in the randomised Stenting of Saphenous Vein Grafts (SOS) trial at 35 months of follow-up (54%) 14 . Similarly, in the Extended Duration of the Reduction of Restenosis In Saphenous vein grafts with Cypher stent (DELAYED RRISC) study 15 , rates of MACE amounted to 58% among SES-treated patients at a median follow-up of 32 months.…”
Section: Discussionsupporting
confidence: 85%
“…First-and secondgeneration DES have been shown to be superior to bare-metal stents with respect to angiographic and clinical restenosis after SVG-PCI. [22][23][24] However, the late restenosis phenomenon after http://circinterventions.ahajournals.org/ Downloaded from Plaque Sealing and Saphenous Vein Grafts SVG stenting has been described with the use of first-generation DES, 25,26 and it is unclear at this time whether this may also occur with the use of newer-generation DES. Reducing late stent restenosis seems to be a key factor in maintaining the potential initial clinical benefits of intermediate SVG lesions plaque sealing.…”
Section: Resultsmentioning
confidence: 99%
“…While concerning, the increased risk of mortality observed in DELAYED RRISC was not replicated in either of the two additional randomized trials in this field. The Stenting of Saphenous Vein Grafts (SOS) trial randomized SVG PCI patients (n = 80; median age, 67 years) to a paclitaxel-eluting stent (Taxus, Boston Scientific, Natick, MA) versus a similar BMS [4]. In the SOS cohort, no significant difference in mortality was observed for DES versus BMS patients (24% vs. 13%, P = 0.2); however, both target vessel revascularization (22% vs. 49%, P = 0.03) and MI (17% vs. 46%, P = 0.01) were significantly lower a HR <1.0 favors DES.…”
Section: Discussionmentioning
confidence: 99%
“…In failing saphenous vein grafts (SVG), drug-eluting stents (DES) have been shown to reduce the incidence of myocardial infarction (MI) and target vessel revascularization (vs. bare metal stents [BMS]) [3,4]; however, in this setting, DES use has been associated with increased mortality in the Death and Events at Long-term follow-up AnalYsis: Extended Duration of the Reduction of Restenosis in Saphenous vein grafts with Cypher stent) (DELAYED RRISC) trial [5]. As a result, clinical equipoise remains, especially among patients with certain high-risk features (e.g., acute coronary syndromes [ACS], de novo lesions, and graft body lesion location).…”
Section: Introductionmentioning
confidence: 99%